Міжнародна співраця у боротьбі з наркоторгівлею у державах Південно-Східної Азії - Кружкова, Єлизавета Максимівна; Kruzhkova, Yelyzaveta Maksymivna (Національний університет "Львівська політехніка", 2024)
У роботі проаналізовано міжнародну взаємодію у сфері боротьби з наркоторгівлею у країнах Південно-Східної Азії. Розглянуто розвиток наркотрафіку у регіоні, спрямовані на боротьбу з ним міжнародно-правові акти, міжнародні організації, серед яких УНЗ ООН, Інтерпол та АСЕАН. Приділено увагу національним та міжнародними стратегіям боротьби з незаконним обігом наркотиків, ключовим викликам у цій сфері та можливостям покращення взаємодії на регіональному та глобальному рівні. Об’єкт дослідження – міжнародна співпраця у боротьбі з наркоторгівлею у державах Південно-Східної Азії. Предмет дослідження – специфіка міжнародної боротьби з наркоторгівлею у державах Південно-Східної Азії. Метою дослідження є аналіз сучасної міжнародної співпраці у боротьбі з наркоторгівлею у державах Південно-Східній Азії. У роботі проаналізовано сучасну міжнародну співпрацю у боротьбі з наркоторгівлею у Південно-Східній Азії. Значну увагу приділено міжнародно-правовій базі, яка контролює незаконний обіг наркотиків, здебільшого ключовим документам ООН – Єдиній конвенції «Про наркотичні засоби» 1961 р. [5], Конвенціям «Про психотропні речовини» 1971 р. [4] та «Проти незаконного обігу наркотичних засобів та психотропних речовин» 1988 р. [6]. У дослідженні окреслено діяльність таких міжнародних організацій, як Управління ООН з наркотиків та злочинності [8], Комісія ООН з наркотичних засобів [3] та АСЕАН [2], які координують боротьбу з наркотиками, забезпечують обмін даними між країнами та реалізують спільні проєкти в регіоні. Зазначено також Політичну декларацію та План дій УНЗ ООН 2009 р., серед ключових елементів регіональної політики у цій сфері [7]. У роботі представлено успішні практики Таїланду та інших країн у боротьбі з наркоторгівлею, які свідчать про результативність поєднання національних ініціатив і міжнародної підтримки у цій сфері [1].

The present study analyzes international cooperation in the fight against drug trafficking in Southeast Asia. The development of drug trafficking in the region, the main international legal acts, and the activities of international organizations, including the UNODC, Interpol, and ASEAN, are considered. A close examination of national and international strategies for combating drug trafficking is undertaken, with particular attention to the key challenges in this area and opportunities for improving cooperation at the regional and global levels. Study object is international cooperation in the fight against drug trafficking in Southeast Asia. Scope of research is the specifics of the international fight against drug trafficking in Southeast Asia. Goal of research is to analyze the current international cooperation in the fight against drug trafficking in Southeast Asia. The present study analyzes current international cooperation in the fight against drug trafficking in Southeast Asia. A substantial amount of attention is allocated to the international legal framework governing drug trafficking, with a particular focus on the pivotal UN documents: the Single Convention on Narcotic Drugs of 1961 [5], the Convention on Psychotropic Substances of 1971 [4], and the Convention against Illicit Traffic in Narcotic Drugs and Psychotropic Substances of 1988 [6]. The study delineates the activities of international organizations such as the United Nations Office on Drugs and Crime [8], the United Nations Commission on Narcotic Drugs [3], and the Association of Southeast Asian Nations [2]. These organizations coordinate the global fight against the illicit drug trade, facilitate data exchange between countries, and implement joint projects in the region. The 2009 UNODC Political Declaration and Plan of Action is also mentioned, constituting an additional pivotal element of regional policy [7]. The document under consideration herein presents the successful practices of Thailand and a number of other countries in the fight against drug trafficking. These practices demonstrate the effectiveness of combining national initiatives and international support [1].
International Cooperation in Combating Drug Trafficking in Southeast Asian Countries
Keywords: 6.291.00.01; Південно-Східна Азія; міжнародна співпраця; наркоторгівля; УНЗ ООН; АСЕАН; конвенція. Перелік використаних джерел та літератури. Прищепа; Я. (2021; грудень 24). Сховали у боксерських грушах. Правоохоронці Таїланду вилучили метам-фетамін на 30 мільйонів доларів. Суспільне Новини. https://suspilne.media/192439-shovali-u-bokserskih-grusah-pravoohoronci-tailandu-vilucili-metamfetamin-na-30-miljoniv-dolariv/ ASEAN Media. (2023). ASEAN best practices: Combatting drug trafficking in Southeast Asia. https://aseanmediadirectory.com/asean-best-practices-drug-trafficking/ United Nations Office on Drugs and Crime (UNODC). (2023). Commission on Narcotic Drugs (CND). https://www.unodc.org/unodc/en/commissions/CND/index.html United Nations. (1971). Convention on psychotropic substances; 1971 (28 pp.). https://www.unodc.org/pdf/convention_1971_en.pdf United Nations. (1961). Single convention on narcotic drugs; 1961 (44 pp.). https://www.unodc.org/pdf/convention_1961_en.pdf United Nations. (1988). United Nations convention against illicit traffic in narcotic drugs and psychotropic substances; 1988 (31 pp.). https://www.unodc.org/pdf/convention_1988_en.pdf United Nations Office on Drugs and Crime (UNODC). (2016). Political declaration and plan of action on international cooperation towards an integrated and balanced strategy to counter the world drug problem (68 pp.). https://www.unodc.org/documents/ungass2016/V0984963-English.pdf United Nations Office on Drugs and Crime (UNODC). (n.d.). About us. https://www.unodc.org/unodc/en/about-unodc/index.html; Southeast Asia; international cooperation; drug trafficking; UNODC; ASEAN; convention